Hadith for beginners: an introduction to major Hadith works and their compilers - Siddiqi, Muhammad Zubair (Goodword Books ; Islamic Vision Ltd. ; IB Publisher Inc. New Delhi, Birmingham, UK, Hicksville, NY, 2010)
A concise introduction to the major Hadith collections and their compilers, offering beginners a foundational understanding of Islamic traditions and teachings.